The appeal of insurance - Clark, Geoffrey, 1959- (University of Toronto Press, 2010)
"Insurance today is a global economic colossus and a fixture in the developed countries of the world. Dependant upon a considerable dose of moral exhortation and enlightened appeal, the insurance industry has become a pervasive agent of social and economic control through its delineation of acceptable (compensated) and unacceptable (uncompensated) risk. The Appeal of Insurance traces the ways in which insurance, over the past three centuries, has grown in concert with a clientele largely of its own making. Drawing on the fields of history, sociology, criminology and economics, these essays break new ground in insurance studies by illuminating the dialectical relationship between the expansion of the insurance business and the public demand for economic and social security."--Pub. desc.